Pro-Resolving Lipid Mediators (SPMs) and Their Actions in Regulating miRNA in Novel Resolution Circuits in Inflammation - Serhan, Charles N.; Recchiuti, Antonio (Frontiers in Immunology, 2012)
Unresolved inflammation is associated with several widely occurring diseases such as arthritis, periodontal diseases, cancer, and atherosclerosis. Endogenous mechanisms that curtail excessive inflammation and prompt its timely resolution are of considerable interest. In recent years, previously unrecognized chemical mediators derived from polyunsaturated fatty acids were identified that control the acute inflammatory response by activating local resolution programs. Among these are the so-called specialized pro-resolving lipid mediators (SPMs) that include lipoxins (LX), resolvins (Rv), protectins (PD), and maresins (MaR), because they are enzymatically biosynthesized during resolution of self-limited inflammation. They each possess distinct chemical structures and regulate cellular pathways by their ability to activate pro-resolving G-protein coupled receptors (GPCRs) in a stereospecific manner. For instance, RvD1 controls several miRNAs of interest in self-limited acute inflammation that counter-regulate the mediators and proteins that are involved in inflammation. Here, we overview some of the biosynthesis and mechanisms of SPM actions with focus on the recently reported miR involved in their pro-resolving responses that underscore their beneficial actions in the regulation of acute inflammation and its timely resolution. The elucidation of these mechanisms operating in vivo to keep acute inflammation within physiologic boundaries as well as stimulate resolution have opened resolution pharmacology and many new opportunities to target inflammation-related human pathologies via activating resolution mechanisms.